O efeito moderador da motiva????o do consumo hed??nico e/ou utilit??rio no comportamento de compra por impulso no varejo - Pugas, Maur??cio Alves Rodrigues (2019)
The origin of this work was the result of a research carried out in Italy in 2017, in which the researchers Silvia Bellini, Maria Grazia Cardinali and Benedetta Grandi studied the determinant aspects of impulse buying in a supermarket retail chain, by the relation of independent variables and mediators. The main objective of this dissertation was to evaluate the moderating effect of the Hedonic and Utilitarian Purchase Motivation on the Impulsive Purchase Behavior, allowing this researcher to create a new model that considers this moderation among the variables of Impulsive Purchase Behavior. The data were collected through the application of a questionnaire in two distinct environments (shoes and clothing stores and supermarkets), and in two moments (before the client enter the store and after the purchase is completed), in a sample of 501 respondents. For the measurement of the variables for estimation of the constructs from the proposed model, we used scales previously tested and validated. Variables frequency analyzes were performed considering the two moments of approach, followed by the presentation of the results of the multivariate analyzes, with the obtaining of adequate results in the initial tests, without evidence of multicollinearity in the independent variables of the model. Then, the proposed model was tested through structural equations models (SEM), taking into account the convergent validity, discriminant analysis, the general indicators of the model, and the path analysis and the hypothesis test. The main objective was assigned, mainly by the analysis of the final mediated model, since the results indicated that, to a great extent, the Impulse Purchase Behavior is affected by the Consumer Purchase Motivation. In general, hedonic motivations minimize the effect of the protection strategies that consumers adopt in order to control their impulsivity during purchases. We believe that this study leaves relevant contributions to theory and managers, as well as limitations and suggestions for further studies. This dissertation also presents considerations, emphasizing the importance of this study, which did not have the intention to finish such a broad theme, but to make a contribution to the campus of knowledge.